Pengaruh Kemampuan Kerja dan Pengalaman Kerja terhadap Kinerja Pegawai Melalui Kesejahteraan Pegawai sebagai Variabel Intervening pada Puskesmas Pasar Bantal - Lusi Apriyanti; Marta Widian Sari; Harmelia Harmelia (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
This study aims to assess and analyze the impact of work ability and work experience on employee performance, with employee welfare as an intervening variable, at the Pasar Pillow Community Health Center. The research employs Structural Equation Modeling (SEM) using the SmartPLS 3.0 analysis tool. The study population and sample consist of employees from the Pasar Pillow Community Health Center. The findings indicate a significant correlation between work ability and employee welfare, as well as between work experience and employee welfare. Additionally, there is a significant association between work ability and employee performance, while no significant relationship is observed between work experience and employee performance. Moreover, there is no significant correlation between employee welfare and employee performance. Furthermore, employee welfare does not act as a mediator between work ability and employee performance, nor does it mediate the relationship between work experience and employee performance.